Additional Cover. (15th December 2021) - Colomban, Philippe; Gironda, Michele; Edwards, Howell G. M.; Mesqui, Viviane
Abstract : The cover image is based on the Special Issue – Research Article The enamels of the first (soft-paste) European blue‐and‐white porcelains: Rouen, Saint‐Cloud and Paris factories: Complementarity of Raman and X‐ray fluorescence analyses with mobile instruments to identify the cobalt ore by Philippe Colomban et al., https://doi.org/10.1002/jrs.6111 .